PET Imaging of Dopamine Neurotransmission During EEG Neurofeedback - Ros, Tomas; Kwiek, Jessica; Andriot, Theo; Michela, Abele; Vuilleumier, Patrik; Garibotto, Valentina; Ginovart, Nathalie (Frontiers in Physiology, 2021)
Neurofeedback (NFB) is a brain-based training method that enables users to control their own cortical oscillations using real-time feed-back from the electroencephalogram (EEG). Importantly, no investigations to date have directly explored the potential impact of NFB on the brain’s key neuromodulatory systems. Our study’s objective was to assess the capacity of NFB to induce dopamine release as revealed by positron emission tomography (PET). Thirty-two healthy volunteers were randomised to either EEG-neurofeedback (NFB) or EEG-electromyography (EMG), and scanned while performing self-regulation during a single session of dynamic PET brain imaging using the high affinity D2/3 receptor radiotracer, [18F]Fallypride. NFB and EMG groups down-regulated cortical alpha power and facial muscle tone, respectively. Task-induced effects on endogenous dopamine release were estimated in the frontal cortex, anterior cingulate cortex and thalamus, using the linearized simplified reference region model (LSRRM), which accounts for time-dependent changes in radiotracer binding following task initiation. Contrary to our hypothesis of a differential effect for NFB vs EMG training, significant dopamine release was observed in both training groups in the frontal and anterior cingulate cortex, but not in thalamus. Interestingly, a significant negative correlation was observed between dopamine release in frontal cortex and pre-to-post NFB change in spontaneous alpha power, suggesting that intra-individual changes in brain state (i.e. alpha power) could partly result from changes in neuromodulatory tone. Overall, our findings constitute the first direct investigation of neurofeedback’s effect on the endogenous release of a key neuromodulator, demonstrating its feasibility and paving the way for future studies using this methodology.